Is Supplementary Pension Beneficial to Human Capital Investment? Evidence from China. Issue 3 (19th February 2022) - Gong, Yalin; Lai, Li; Chan, Kam C.; Xia, Xiaolan
ABSTRACT: We examine the impact of a supplementary pension insurance program (SPIP) and short-term compensation on firm-level human capital investment using a sample of Chinese firms from 2007 to 2018. The findings suggest that both SPIP and short-term compensation have positive effects on human capital investment, and the magnitude of SPIP is stronger than that of short-term compensation. Further analysis suggests that the impact of SPIP on human capital investment in a firm is magnified when the firm has high-quality employees. Our findings are robust after accounting for potential endogeneity concerns. When compared with short-term compensation, SPIPs contribute more to establishing a long-term relationship between a firm and its employees, which stimulates human capital investment.